2021
DOI: 10.3390/ijerph182111477
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Alcohol Use: Does the Type of Leisure Activity Matter? A Cross-National Study

Abstract: The main objective of this study was to analyze the relationship between structured, unstructured, and family leisure activities on the frequency of adolescent alcohol intake across three different countries (Spain, Peru, and The Netherlands). The self-control of adolescents was also investigated as a moderator in the relationship between leisure activities and alcohol consumption. Methodology: This research involved 4608 adolescents aged between 12 and 17 from three countries (Spain, Peru, and The Netherlands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
5
0
3
Order By: Relevance
“…The lack of structure also provides time and opportunities for adolescents to engage in problem behavior. Consistent with routine activity theory, studies conducted in the United States, European, and South American contexts have found unsupervised, unstructured time with peers to be linked to higher alcohol and marijuana use during the middle and high school years (Albertos et al, 2021 ; Badura et al, 2018 ; Lee & Vandell, 2015 ).…”
Section: Out‐of‐school Settings As Risk and Protective Factorsmentioning
confidence: 88%
See 1 more Smart Citation
“…The lack of structure also provides time and opportunities for adolescents to engage in problem behavior. Consistent with routine activity theory, studies conducted in the United States, European, and South American contexts have found unsupervised, unstructured time with peers to be linked to higher alcohol and marijuana use during the middle and high school years (Albertos et al, 2021 ; Badura et al, 2018 ; Lee & Vandell, 2015 ).…”
Section: Out‐of‐school Settings As Risk and Protective Factorsmentioning
confidence: 88%
“…These settings differ in their structure, potential for adult supervision, and opportunities for different types of interactions with adults and with peers. A robust literature has documented the relations between adolescents' time in out‐of‐school settings and their alcohol and marijuana use in high school through cross‐sectional and short‐term longitudinal studies (Adachi‐Mejia et al, 2014 ; Albertos et al, 2021 ; Kwan et al, 2014 ; Lee & Vandell, 2015 ). What is less clear is whether there are lingering long‐term effects of adolescents' time in out‐of‐school settings on their substance use in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…En línea con investigaciones previas, la edad influyó de manera directa en la frecuencia de ceea: los adolescentes más grandes son quienes presentaron de manera más frecuente esta modalidad de consumo (41,43,44,80). A su vez, se observó un efecto significativo y positivo de la edad sobre las ea positivas de sociabilidad y negativo sobre las ea negativas de riesgo y agresividad que, a su vez, influyó en una mayor o menor frecuencia de ceea, respectivamente.…”
Section: Discussionunclassified
“…Más allá de estas diferencias metodológicas, la alta prevalencia de este tipo de consumo resulta preocupante, ya que estudios previos han mostrado que quienes exhiben este tipo de consumo experimentan una mayor cantidad de consecuencias negativas derivadas por el consumo de alcohol (5,6,82,83). Asimismo, los resultados evidenciaron un consumo de alcohol similar entre varones y mujeres, lo cual coincide con estudios nacionales e internacionales (1,43,45,46,84). Esta ausencia de diferencias en la adolescencia, junto con el aumento en la cantidad y la frecuencia de consumo de alcohol por parte de las mujeres jóvenes, que ha derivado en el acortamiento de la brecha en el consumo de hombres y mujeres jóvenes, es un factor de riesgo particularmente para las mujeres (85)(86)(87)(88).…”
Section: Discussionunclassified
See 1 more Smart Citation